Depression, Irritability, and Anxiety in Women with Premenstrual Dysphoric Disorder. (July 2013) - Ko, Chih-Hung; Long, Cheng-Yu; Chen, Su-Yin Chen I-Ju; Huang, Tzu-Hui; Yen, Ju-Yu
Objective: Depression, anxiety, and irritability are the three most studied symptoms of premenstrual dysphoric disorder (PMDD). This study aimed to assess the premenstrual exacerbation of these symptoms and their role in the diagnosis or functional impairment of PMDD. Methods: We recruited women with PMDD not undergoing any treatment and control subjects from the community. The diagnosis of PMDD was based on a positive score on the Premenstrual Symptoms Screening Tool and confirmed by psychiatric interviews and questionnaire follow-up for three menstrual cycles. A total of 67 women with PMDD and 75 control subjects participated the survey and reach the final analysis. They complete the Center for Epidemiological Studies, the Chinese Version of the Buss-Durkee Hostility Inventory-Short Form, and the Penn State Worry Questionnaire in both the premenstrual and follicular phases. Results: Women with PMDD, but no controls, demonstrate the premenstrual exacerbation of these three symptoms. Depression was the most prominent feature of the PMDD diagnosis while irritability was most frequently associated with functional impairment. Conclusions: Depression and irritability should be properly evaluated and treated among women with PMDD.